SAMARQAND JADIDCHILIGIDAGI ASOSIY PRAGMATIK YO‘NALISHLARIDA TA’LIM-TARBIYA MASALALARINING AKS ETISHI - Negmatova, Sh.Sh. (SCIENCE and SOCIETY, 2025)
This article analyzes the reflection of educational issues in the main pragmatic directions of Samarkand Jadidism. At the same time, the article discusses the literary innovations, themes, genres, forms, and styles of Jadid writers.
Keywords: jadidism; pragmatism; education; upbringing; literary genre; national dramaturgy